Pengembangan Media Pembelajaran Interaktif Rantai Natura pada Materi Rantai Makanan untuk Pembelajaran IPAS di MI Aswaja 1 Tamban Kabupaten Kediri - Khalimatur Rosidah; Hafidz Rosyidiana (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2026)
Interactive learning media is needed to support an interactive and interesting learning process. However, in reality there are still many classroom learning methods that only use lecture methods, so that students feel bored and have difficulty understanding indirect materials such as food chains. This study aims to develop an interactive learning media Rantai Natura, determine its feasibility, and obtain responses from class V students of MI Aswaja 1 Tamban. This study uses the Research and Development (R&D) method with the ADDIE model. The results of the study show that the Rantai Natura media was successfully developed well and obtained a very feasible category, with a score of 86% from material experts and 90% from media experts. Student responses also showed very good results with a percentage of 85.50%. Thus, this media is suitable for use to support science learning on food chain material.